Law's rule : the nature, value, and viability of the rule of law - Postema, Gerald J. (New York, NY : Oxford University Press, 2022)
The rule of law, once widely embraced and emulated, now faces serious threats to its viability. To answer these fundamental threats, we first must return to its foundational principles. This book articulates a coherent framework and foundation for thinking about the rule of law and planning strategies for building and defending it against serious challenges to its intelligibility, relevance, and normative force.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 22, 2022).
Keywords: Rule of law -- Philosophy; Law (Philosophical concept); Law; Jurisprudence & general issues